Adherence to Head-of-Bed Elevation in Traumatic Brain Injury: An Audit - Chitteti, Pragnitha; George, Ajish Sam; Nair, Shalini; Karuppasamy, Reka; Joseph, Mathew (Journal of Neuroanaesthesiology and Critical Care, 2022)
Background An important factor affecting the outcome of traumatic brain injury (TBI) is the early management of raised intracranial pressure (ICP). Head-of-bed elevation (HBE) is a simple and effective method to reduce ICP and prevent aspiration in head injury.Methods This audit was carried out in a level one trauma center. All adult TBI patients were included in the study except patients who had relative contraindication to HBE, managed in prone or Trendelenburg position or who were able to be seated themselves. Patients were observed twice daily, to check adherence to HBE. Adequate HBE angle was referred as an angle of 20 to 30 degrees. A digital protractor was used to measure the head-end angle. Following the first audit cycle, after discussion with nursing staff, a bedside checklist was formulated and two postintervention audit cycles were carried out.Results The first cycle showed that 40.35% of patients had inadequate HBE. Following implementation of the checklist, this percentage dropped to 11.27 and 7.5% in the second and third cycles, respectively. Agitation (p-value = 0.038) and Glasgow coma scale at admission (p-value = 0.028) were found to be confounders for adherence to HBE.Conclusion Agitation among mild and moderate TBI patients contributed to noncompliance for HBE. There was an increasing trend in adherence to maintaining adequate HBE following the use of a bedside checklist. Sustainability of improvement was confirmed with third audit cycle.
Keywords: head-end elevation; audit; neurocritical care; raised intracranial pressure; traumatic brain injury